Intregasi Konsep Kafa'ah Terhadap Peminangan Menurut Aadat Jawa - umam, syafiul; Arifin, Mochammad (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
The understanding of kafaah in Javanese traditional marriages is an internalization of Islamic values ​​as an assimilation of Javanese customs. There is a Javanese traditional marriage process with various considerations, so the concept of kafaah can be used as an option for consideration that is humanistic and beneficial. In fact, the traditional understanding regarding proposals in Javanese customs is a form of local wisdom that becomes a habit, but also not a little too much, causing problems in the future. It is also something that should be realized together, that goodness should be seen and carried out from the consideration of religious aspects, which is expected to minimize disputes. This type of research uses library research, a series of research activities related to library data collection methods. The analysis includes data presentation and discussion is carried out qualitatively and conceptually. Data analysis must always be linked to the context and construct of the analysis. Departing from the legal basis of kafaah in Islam, the size of the concept of kafaah and efforts to integrate the proposal in Javanese customs are expected to create religious considerations and awareness of the proposal process. So that it can minimize problems that arise due to elements of habit that are too prioritized. Integration is one of the paths towards policy in determining potential life partners.